DESCRIPTION OF THE QUALITY OF LIFE OF STROKE PATIENTS - Suprayitno, Edy (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: Stroke is a disease that causes the highest mortality. Stroke causes disruption of activity and changes in quality of life. It is necessary to study the quality of life of stroke patients. The purpose of this study was to determine the description of the quality of life of patients suffering from stroke.Methods: This type of research is descriptive with accidental sampling method, data was taken for 1 month and obtained 33 samples. Inclusion criteria: stroke patients treated in the internal medicine ward, fully conscious and able to speak. The questionnaire used the SS-QOL questionnaire (5 domains of quality of life: energy, family roles, language, mobility, mood, personality, self-care, social role thinking, upper extremity function, vision, work/productivity).Results: The results showed that the good category of quality of life was the role of family, mood and personality. The domains of language skills, social roles, thinking/cognitive, extremity function, vision, work. Productivity in the medium category. While the domains of mobility, self-care and low energy abilities.Conclusion: it is necessary to monitor and fulfill patient care needs so that the quality of life of stroke patients is increasing.